PENGARUH FINANCIAL LITERACY DAN FINANCIAL ATTITUDE TERHADAP PERILAKU PERENCANAAN KEUANGAN MASA PENSIUN PADA GENERASI SANDWICH DI SURABAYA - Tabita, Jennifer; Marlina, Maria Asumpta Evi (Media Akuntansi dan Perpajakan Indonesia, 2023)
Along with the times, a new generation emerged which became a problem in the world, namely the sandwich generation. One of the factors causing the emergence of the sandwich generation is the failure in financial planning and management for retirement in the previous generation. This study aims to examine the effect of financial literacy and financial attitude on retirement financial planning behavior. The respondents were 100 people of the sandwich generation in Surabaya who were taken by purposive sampling method. The analysis used is multiple regression analysis. The independent variables are financial literacy and financial attitude, while the dependent variable is retirement financial planning behavior. The results of the F test indicate that the regression model used in the study is declared feasible. The results of the t-test analysis show that the variables of financial literacy and financial attitude partially have a significant positive effect on the retirement financial planning behavior of the sandwich generation in Surabaya. So it can be concluded that if each financial literacy and financial attitude are getting better, they will be able to improve financial planning behavior in retirement.